Penggunaan Action Script pada Video Profil Desa Kedunggede - Wardhani, Melinia Indah; Prasetyo, Muhamad Awiet Wiedanto (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2022)
Kedunggede Village is one of the villages located in Lumbir District, Banyumas Regency. In this area there are still many forests which are usually planted with several types of plants such as pine and teak. In addition to natural resources, there are also home industries such as brick making, tempe chips making, companies engaged in wood, cattle breeding, and companies engaged in antique houses. There is a lot of potential that exists but so far it has not been well documented. This study aims to produce a video profile of Kedunggede village as a publication media so that later it can be known by the wider community. The development method used consists of Pre-Production, Production, and Post-Production. In making this profile video, there is the use of Action Script and the application of Cinematography Techniques in video capture. The other techniques used are Hyperlapse and Timelapse. For publication media using Youtube with a video duration of 6 minutes. Keywords: Video Profile, Action Script, Cinematography Techniques